2007
DOI: 10.1103/physrevb.76.054204
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic correlation between fragility and bulk modulus in metallic glasses

Abstract: A systematic study on the available data of 26 metallic glasses shows that there is an intrinsic correlation between fragility of a liquid and bulk modulus of its glass. The underlying physics can be rationalized within the formalism of potential energy landscape thermodynamics. It is surprising to find that the linear correlation between the fragility and the bulk-shear modulus ratio exists strictly at either absolute zero temperature or very high frequency. Further analyses indicate that a real flow event in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 69 publications
3
47
0
2
Order By: Relevance
“…However, compared with the mean tensile stress, the shear-induced dilation in amorphous alloys is a secondary effect. 46,47 The volume dilation caused by deviatoric stress is significantly smaller than that caused by mean tensile stress, so we only consider mean tensile stress in this model.…”
Section: Decrease Of Activation Barriermentioning
confidence: 99%
“…However, compared with the mean tensile stress, the shear-induced dilation in amorphous alloys is a secondary effect. 46,47 The volume dilation caused by deviatoric stress is significantly smaller than that caused by mean tensile stress, so we only consider mean tensile stress in this model.…”
Section: Decrease Of Activation Barriermentioning
confidence: 99%
“…Recently, it is found that the elastic moduli scaled with V m show better correlations with the thermal and mechanical properties for metallic glasses [17][18][20][21]. Thus, the characteristic volume could be an important parameter involved in the flow event in glass transition and glass.…”
mentioning
confidence: 99%
“…These BMGs cover many typical alloy systems, including Zr-, Cu-, Ca-, Mg-, Ni-, Fe-, and rare earth elements Fig. 1(b) confirms that the N involved in the cooperative flow event for various metallic glasses is almost the same.Based on above scaling laws and elastic model, we propose that it is the flow activation energy density (ρ E ), not the flow activation energy itself, correlates with the elastic moduli as:The extended elastic model means that the energy per volume needed in glass transition or in STZ in metallic glass is proportional to the elastic moduli.Previous elastic models [1] suggest that the atoms or atomic groups go through pure shearing displacement which is independent of K, and the ρ E depends only on G.Recent works [18,20] and the jamming model of granular systems [22] find that both shear and dilatation are involved in the flow during glass transition and deformation.Next, we further justify the flow activation energy density ρ E relates not to G or K but both G or K. That is, the flow event relate to both shearing transformation (corresponding to volume-preserving G) and dilatation (corresponding to volume-nonpreserving K). At T g , the ∆F/T g should be the same for all glasses that is independent of Poisson's ratio or other moduli [3].…”
mentioning
confidence: 99%
See 2 more Smart Citations